2002
DOI: 10.1302/0301-620x.84b2.12599
|View full text |Cite
|
Sign up to set email alerts
|

A simple guide to determine the magnification of radiographs and to improve the accuracy of preoperative templating

Abstract: Templates are used in the preoperative planning of many orthopaedic procedures. The magnification of the bones on preoperative radiographs can vary despite using standardised radiological techniques. Templates will give misleading measurements unless this magnification is quantified. A coin may be used to calculate the magnification, with significant improvement in the accuracy of templating (p = 0.05). A group of patients undergoing uncemented arthroplasty of the hip was at high risk for intraoperative fractu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(58 citation statements)
references
References 6 publications
1
51
0
6
Order By: Relevance
“…This data was not available in the current study so a standard magnification factor of 20% was used to adjust the actual measurements taken from the radiographs. However, this is the standard magnification used in most templating systems and consistent with other studies [3,10,14,15].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This data was not available in the current study so a standard magnification factor of 20% was used to adjust the actual measurements taken from the radiographs. However, this is the standard magnification used in most templating systems and consistent with other studies [3,10,14,15].…”
Section: Discussionsupporting
confidence: 88%
“…The distance on the post-operative side was compared to the contralateral limb which was assumed to be equal to the initial length of the operated limb before development of joint disease. Magnification was adjusted for by using a standard estimation of 20% magnification consistent with the literature [3,10,14,15]. All measurements were made on the initial post-operative radiographs and were made to the nearest millimetre by a single observer not involved in the surgical procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Different methods of scaling digital radiographs have been described and investigated to improve planning accuracy [17][18][19][20][21]. Accurate positioning of the reference ball at the level of the joint is crucial to achieving the greatest possible referencing reliability [17,22,23]. Another pre-requisite is precisely adjusted pelvic overviews and/or radiographs of the knee joint in two planes.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Digital templating offers a way to avoid these errors with quicker, more cost-efficient templating that can be easily stored for future reference. 16 It has also been shown that the accuracy of pre-operative digital templating in knee and hip arthroplasty meets or exceeds that of analogue templating, thus giving more support for the use of entirely digital techniques.…”
Section: Introductionmentioning
confidence: 99%